Encapsulation of Vitamins a and E as Spray-Dried Additives for the Feed Industry - Bustos-Cerda, R; Matiacevich, S (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Encapsulated fat-soluble powders containing Vitamin A (VA) and E (VE) were prepared as a feasible additive for extruded feed products. The effect of the encapsulating agents (Capsul-CAP®, sodium caseinate-SC) in combination with Tween 80 (TW) as an emulsifier and maltodextrin (MD) as a wall material on the physicochemical properties of emulsions and powders was evaluated. First, nanoemulsions containing MD:CAP:TW:VA/VE and MD:SC:TW:VA/VE were prepared and characterized. Then, powders were obtained by means of spray-drying and analyzed in terms of the product yield, encapsulation efficiency, moisture content, porosity, surface morphology, chemical structure, and thermal properties and thermo-oxidative/thermal stability. Results showed that although nanoemulsions were obtained for all the compositions, homogeneous microcapsules were found after the drying process. High product yield and encapsulation efficiency were obtained, and the presence of the vitamins was corroborated. The characteristics of the powders were mainly influenced by the encapsulating agent used and also by the type of vitamin. In general, the microcapsules remained thermally stable up to 170 °C and, therefore, the proposed encapsulation systems for Vitamins A and E were suitable for the preparation of additives for the feed manufacturing through the extrusion process. © 2020 by the authors.